Undated chapters five, six, and seven for use with principles of auditing & other assurance services - Whittington, Ray, 1948-; Pany, Kurt (New York : McGraw-Hill, 2006)
The auditing standards board recently issued a series of new statements on auditing standards. These are the long-awaited risk assessment standards. While the fifteenth edition of the text includes coverage of most of the basic concepts included in these new standards, we have included revisions of the most directly affected chapters in this update to more thoroughly consider the new standards. Accordingly, this update includes revisions of chapters 5 trough 7 on audit evidence, audit planning, and internal control, respectively. --
Incluye índice.
Keywords: AUDITORIA; AUDITORIA INTERNA; AUDITORIA -- NORMAS